2021
DOI: 10.3390/biology10030183
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous Effects of SiO2 Nanoparticles on Liver and Kidney Functions, Histopathology Characteristics, and Transcriptomic Responses in Nile Tilapia (Oreochromis niloticus) Juveniles

Abstract: The current investigation assessed the impacts of sub-lethal concentrations of silicon dioxide nanoparticles (SiO2NPs) on hepato-renal functions, histopathological characteristics, and gene transcription in gills and liver of Nile tilapia juveniles. Fish were exposed to 20, 40, and 100 mg/L of SiO2NPs for 3 weeks. Pairwise comparisons with the control group showed a significant dose-dependent elevation in serum ALP, ALT, and AST enzyme activities as well as blood urea and creatinine levels in SiO2NP-intoxicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Some in vivo and in vitro studies have shown that SiO 2 NPs can cause toxicity to different organs in the human body; toxicity has been demonstrated in lung epithelial cells [ 9 ], liver cells [ 10 ], intestinal cells [ 11 ], the lungs [ 12 ], and kidneys [ 13 ]. In addition, SiO 2 NPs were found to induce genotoxicity and alterations in gene and protein expression [ 12 , 14 ], and Chen et al [ 15 ] reported that SiO 2 NPs can induce cornea toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Some in vivo and in vitro studies have shown that SiO 2 NPs can cause toxicity to different organs in the human body; toxicity has been demonstrated in lung epithelial cells [ 9 ], liver cells [ 10 ], intestinal cells [ 11 ], the lungs [ 12 ], and kidneys [ 13 ]. In addition, SiO 2 NPs were found to induce genotoxicity and alterations in gene and protein expression [ 12 , 14 ], and Chen et al [ 15 ] reported that SiO 2 NPs can induce cornea toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, there was no significant difference in INF-γ concentration among the groups, and HSP-70 was decreased in the HT and HL groups compared with the control group. In a similar sense, the mRNA expression levels of HSP-70 were increased of the Nile tilapia when exposed to toxicants and stressors ( Abdel-Latif et al, 2021a , b ). Additionally, previous research revealed that probiotics Clostridium butyricum could similarly increase the expression of the IL-10 and HSP-70 in weaning rex rabbits ( Liu et al, 2019 ) and colon cancer HT-29 cells ( Andriamihaja et al, 2009 ; Meng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 86%
“…The literature (Lu et al, 2010;Yu et al, 2012;Fu et al, 2013;Isoda et al, 2013;Hassankhani et al, 2015;Chatterjee et al, 2016;Abdelhalim et al, 2018;Li et al, 2018;Abdel-Latif et al, 2021;Sun et al, 2021) and our previous studies (Lu et al, 2010;Yu et al, 2012;Fu et al, 2013;Isoda et al, 2013;Hassankhani et al, 2015;Chatterjee et al, 2016;Abdelhalim et al, 2018;Li et al, 2018;Abdel-Latif et al, 2021;Sun et al, 2021) have shown that silica particles with particle sizes of 10-1000 nm cause significant damage to the liver, whereas particles with sizes greater than 100 nm cause significant damage to the kidney. To study the effect of particles on the liver, we selected MSNs with an average particle size of 80 nm with a normal particle size distribution.…”
Section: Discussionmentioning
confidence: 84%